The Effectiveness Of Target Play Method Management In Improving The Basketball Shooting Ability Of Junior High School Students - Nazalus Syobri; Lalu Hulfian (Journal Management of Sport, 2025)
This study aims to examine the effect of the target game training method on the shooting ability of junior basketball players at the SMPN 1 Montong Gading in 2024. The research utilized a quasi-experimental approach with a control group pretest-posttest design. A total of 24 participants were selected through purposive sampling from the club’s junior team. The instrument used was the under-basket shooting test, in which players attempted as many accurate shots as possible within 30 seconds. The intervention was conducted over 4 weeks with 12 training sessions. Statistical analysis using the paired sample t-test showed a significant improvement in players' shooting performance. The mean pretest score was 15.5, which increased to 16.58 in the posttest. The result of the t-test revealed a t-value of 3.223 with a significance level of 0.008 (p < 0.05), indicating a significant difference. In contrast, the control group showed no significant improvement. These findings demonstrate that the target game method is effective in enhancing shooting skills by increasing players’ engagement, motivation, and shooting repetition in a fun and active learning environment. This method supports the principles of Teaching Games for Understanding (TGfU) and is recommended for use in youth basketball training programs.